Innovative alignment of sprinting prostheses for persons with transfemoral amputation: Exploratory study on a gold medal Paralympic athlete - Migliore, G. L.; Petrone, N.; Hobara, H.; Nagahara, R.; Miyashiro, K.; Costa, G. F.; Gri, A.; Cutti, A. G. (Prosthetics and Orthotics International, 2020)
Background: Recommendations for the alignment of the socket and foot in the sprinting prosthesis of athletes with transfemoral amputation are either based on walking biomechanics or lack public scientific evidence. Objectives: To explore the biomechanical changes and the sensations of a gold medal Paralympic sprinter, while running with three bench alignments: a conventional reference (A0), an innovative alignment based on the biomechanics of elite able-bodied sprinters (A2), and an intermediate alignment (A1). Study design: Single subject with repeated measures. Methods: A1 and A2 feature a progressively greater socket tilt and a plantar-flexed foot compared to A0. The 30-year-old female athlete trained with three prostheses, one per alignment, for at least 2 months. We administered a questionnaire to collect her impressions. Then, she ran on a treadmill at full speed (5.5 m/s). We measured the kinematics and moments of the prosthetic side, and the ground reaction forces of both sides. Results: A2 reduced the prosthetic side hip extension at foot-off while preserving hip range of motion, decreased the impulse of the hip moment, and increased the horizontal propulsion, leaving sufficient margin to prevent knee buckling without increasing sound side braking forces. Biomechanical outcomes matched well with subjective impressions. Conclusions: A2 appears promising to improve the performance and comfort of sprinters with transfemoral amputation, without compromising safety. Clinical relevance: Observation of elite able-bodied sprinters led to the definition of a new specific alignment for the sprinting prosthesis of athletes with transfemoral amputation, which appears promising to improve performance and comfort, without compromising safety. This may constitute a major improvement compared to alignments based on walking biomechanics.